2020
DOI: 10.1108/cw-09-2019-0117
|View full text |Cite
|
Sign up to set email alerts
|

Load balancing in the internet of things using fuzzy logic and shark smell optimization algorithm

Abstract: Purpose Based on the positive features of the shark smell optimization (SSO) algorithm, the purpose of this paper is to propose a method based on this algorithm, dynamic voltage and frequency scaling (DVFS) model and fuzzy logic to minimize the energy consumption of integrated circuits of internet of things (IoT) nodes and maximize the load-balancing among them. Design/methodology/approach Load balancing is a key problem in any distributed environment such as cloud and IoT. It is useful when a few nodes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In line with, under 1000 iterations, the C3SOA-LS technique has offered fitness values of 0.1160, 0.0808, and 0.0382 on runs 1-3 correspondingly. [18,19]. The results indicated that the C3SOA-LS model has offered better fitness over the other methods.…”
Section: Performance Analysismentioning
confidence: 99%
“…In line with, under 1000 iterations, the C3SOA-LS technique has offered fitness values of 0.1160, 0.0808, and 0.0382 on runs 1-3 correspondingly. [18,19]. The results indicated that the C3SOA-LS model has offered better fitness over the other methods.…”
Section: Performance Analysismentioning
confidence: 99%
“…It uses the three algorithms, Particle Swarm Optimization, Simulated Annealing and Genetic algorithm, to develop the load balancing methodology. They try to address the problems of unbalanced load and lengthier turnaround time in microservices container applications with the help of a load model which combines the service discovery and performance monitoring of the server ecosystem [12]. They made use of the Optimized Ant Colony algorithm for this purpose.…”
Section: Related Researchmentioning
confidence: 99%
“…In recent times, Internet of Things (IoT) was developed as the most important revolution in information and communication technology (ICT) production [1]. By IoT, Internet connections extended over standard smart devices namely smartphone and tablet for different range of devices (machine, vehicle, sensors, and so on.)…”
Section: Introductionmentioning
confidence: 99%